Personality disorders: patient characteristics and level of outpatient treatment service. (4th July 2017) - Simonsen, Sebastian; Heinskou, Torben; Sørensen, Per; Folke, Sofie; Lau, Marianne Engelbrecht
Abstract: Background: In this naturalistic study, patients with personality disorders ( N  = 388) treated at Stolpegaard Psychotherapy Center, Mental Health Services, Capital Region of Denmark were allocated to two different kinds of treatment: a standardized treatment package with a preset number of treatment hours (basic hospital service) and 2: a specialized treatment program for the most severely affected patients without a predetermined restricted number of treatment hours and significantly more individual psychotherapy (regional specialized hospital services). Aims: To investigate patient characteristics associated with clinicians' allocation of patients to the two different personality disorder services. Methods: Patient characteristics across eight domains were collected in order to study whether there were systematic differences between patients allocated to the two different treatments. Patient characteristics included measures of symptom severity, personality pathology, trauma and socio-demographic characteristics. Significance testing and binary regression analysis were applied to identify important predictors. Results: Patient characteristics on fifteen variables differed significantly, all in the expected direction, with patients in regional specialized hospital services showing more pathology and psychosocial problems. In the regression model, only age and two variables capturing psychosocial functioning remained significant predictors of allocation. Discussion: The finding that younger age was the most significant predictor of longer treatment replicates an earlier finding of allocation to treatment for personality disorder. Overall, this study therefore lends further support to the importance of demographic and social contextual factors in clinicians' allocation of patients to different treatment services for personality disorder.